2022
DOI: 10.1021/acs.iecr.1c04123
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Experimental and Computational Study on the Shuttle Mechanism of Piperazine for the Enhanced CO2 Absorption in Aqueous Piperazine Blends

Abstract: Piperazine (PZ) blends containing PZ and monoethanolamine (MEA)/N-methyldiethanolamine (MDEA)/2-amino-2-methyl-propanol (AMP) were experimentally and computationally investigated to analyze their potential capabilities for CO2 capture, and the shuttle mechanism of PZ for enhanced CO2 absorption were verified. In experiments, the concentration of both PZ and MEA/MDEA/AMP were varied to show the effect of concentration ratio and the influence of amine components on the CO2 absorption rate and capacity. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In each position, the O-H functional group is attached to a carbon atom, which is sterically hindered. Additionally, when atoms are close together, the energy of the covalent bonds that keep the atoms together in the molecule increases [40,41]. Due to the increased energy, breaking the chemical bond of the O-H functional groups of the MDEA molecule for generating OḢ radicals is more complex than in water, which is not considered a steric hindrance.…”
Section: Hplc Analysis Of Aqueous Mdea Solution Blended With Tamentioning
confidence: 99%
“…In each position, the O-H functional group is attached to a carbon atom, which is sterically hindered. Additionally, when atoms are close together, the energy of the covalent bonds that keep the atoms together in the molecule increases [40,41]. Due to the increased energy, breaking the chemical bond of the O-H functional groups of the MDEA molecule for generating OḢ radicals is more complex than in water, which is not considered a steric hindrance.…”
Section: Hplc Analysis Of Aqueous Mdea Solution Blended With Tamentioning
confidence: 99%
“…MDEA, and AMP to study their CO 2 absorption capacity. 9 It was found that the addition of PZ could greatly improve the absorption rate and capacity of CO 2 . The absorption-desorption ability of CO 2 was studied by mixing MEA with tertiary amines.…”
Section: Introductionmentioning
confidence: 99%